Deviance, Labelling Theory and the Concept of Scale - Raybeck, Douglas (Anthropologica, 2022)
While sociologists of various theoretical persuasions have tended to construct theories of deviance which neglect empirical, cross-cultural data, anthropologists have tended to focus on social norms and have (with rare exceptions) neglected the whole topic. Anthropologists' antidote to sociology's focus on complex societies may lie in the concept of societal scale, and its relationship to the perception, conceptualization, creation and treatment of deviance. The currently fashionable labelling theory is tested according to these principles. Its core concepts such as the "creation" of deviance by labelling, and secondary deviance, have been constructed solely on the basis of data from complex societies. In small-scale societies, where there is much interdependence and strong interrelationships, there is reluctance to label offenders, rather than specific actions, as deviants. There are few occurrences of secondary deviance, whereby the individuals accept and play the deviant role with which they have been labelled. In general terms, deviance is "soft" rather than "hard" in the sense that it does not threaten the social order. In rare cases of hard deviance, the labelling process occurs. Small units in complex societies (e.g., island fishermen) often exhibit patterns of interdependency and attitudes towards deviance which recall those present in hunter-gatherer bands or the villages of swidden cultivators. The paper's argument is sustained by numerous ethnographic illustrations, which include the author's own observations during his fieldwork in Kelantan.